2019
DOI: 10.1007/s13197-019-03746-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving 3-phenyllactic acid production of Lactobacillus plantarum AB-1 by enhancing its quorum-sensing capacity

Abstract: 3-Phenyllactic acid (PLA) is a novel and natural antimicrobial compound. However, the concentration of PLA produced by native microbes was rather low. To enhance the production of PLA of Lactobacillus plantarum AB-1, the microcapsules of L. plantarum AB-1 cells with a high quorum-sensing capacity was established and investigated. In addition, the relation between PLA production and quorum sensing was further investigated and confirmed by adding the exogenous 4,5-dihydroxy-2,3-pentanedione (DPD, AI-2 precursor)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This conclusion was consistent with the result of lactic acid and PLA production by extracellular accumulation of SS-128 and Δ luxS /SS-128. Yang et al reported that exogenous DPD could promote the growth and the production of PLA of L. Plantarum AB-1 cells [ 57 ]. Similarly, our data suggest that the lactic acid and PLA production of L. plantarum SS-128 was regulated by the AI-2/LuxS system.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was consistent with the result of lactic acid and PLA production by extracellular accumulation of SS-128 and Δ luxS /SS-128. Yang et al reported that exogenous DPD could promote the growth and the production of PLA of L. Plantarum AB-1 cells [ 57 ]. Similarly, our data suggest that the lactic acid and PLA production of L. plantarum SS-128 was regulated by the AI-2/LuxS system.…”
Section: Discussionmentioning
confidence: 99%
“…Alginate gel's mechanical and physicochemical properties can be further improved by forming an electrostatic complex membrane with a polycation, such as chitosan ( 50 ). Previous studies successfully encapsulated L. plantarum, Escherichia coli , and B. longum ( 28 , 51 , 52 ) into microgels containing alginate and chitosan. In the current study, similar strategies were used to prepare L. rhamnosus microgels using alginate and chitosan as the wall materials.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 3-Phenyllactic acid is an organic acid widely found in honey and foods fermented by lactic acid bacteria. It is mainly produced by lactic acid bacteria through the degradation of phenylalanine, has more vigorous antibacterial activity than other organic acids, and is an ideal antibacterial compound [ 54 , 55 ]. Thus, in addition to its role in enhancing antioxidant activity, NCG seems to promote antibacterial activity in pregnant sows, something that should be validated in further studies.…”
Section: Discussionmentioning
confidence: 99%